DIFFERENTIAL DIAGNOSIS OF ACUTE DIFFUSE ENCEPHALOMYELITIS (ADEM) AND MULTIPLE SCLEROSIS (MS) - CASE REPORT - Marcin Narloch; Marcelina Kurek; Weronika Skrzypek; Szymon Skrzypek; Natalia Domańska; Wiktoria Garbacz; Anna Gryc; Zuzanna Rabczak (International Journal of Innovative Technologies in Social Science, 2025)
Acute Disseminated Encephalomyelitis (ADEM) is an acute, immune-mediated demyelinating disorder of the central nervous system, primarily affecting children between 3 and 7 years of age. It typically occurs 1–3 weeks after a viral, bacterial, or post-vaccination infection. Clinically, it presents with multifocal neurological deficits and encephalopathy, which may include altered consciousness, seizures, or cognitive disturbances. MRI shows widespread demyelinating lesions, mainly in the subcortical white matter. Laboratory findings may include elevated CRP, ESR, leukocytosis, and CSF pleocytosis. Treatment involves high-dose intravenous corticosteroids, with intravenous immunoglobulin or plasma exchange used in severe or refractory cases. Though usually monophasic, up to 25% of patients may experience relapses. Some children may require ICU care and early rehabilitation to address cognitive, motor, or speech deficits, highlighting the importance of timely diagnosis and management.